Food contact component and surface treatment method of food contact component

By using metal materials in food contact components, instantaneous heat treatment and titanium oxide diffusion and penetration are performed to form a catalyst layer, solve the problem of use of fluorine resin materials, and achieve efficient anti -sourness, corrosion resistance, rust resistance, abrasion resistance and antibacterial effects Essence

CN112384112BActive Publication Date: 2025-01-28FUJI KIHAN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201880095508.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-20
Filing Date
2018-11-27
Publication Date
2025-01-28
Estimated Expiration
2038-11-27

AI Technical Summary

Technical Problem

In the prior art, the use of fluororesin materials in food contact members has problems such as difficult processing, poor adhesion, peeling of coating films, and toxic gases are generated during heating, which makes maintenance complicated.

Method used

Using food contact components composed of metal or metal materials, through instantaneous heat treatment to form a smooth arc -shaped concave place of non -sharp convex parts, and the titanium oxide diffusion penetrates into the surface, spray titanium or titanium alloy powder to form a catalyst layer to form a catalyst layer Essence

Benefits of technology

The anti -pollution, corrosion resistance, rust resistance, abrasion resistance and antibacteriality of food contact components, avoiding foreign objects caused by the peeling of coating membranes into food problems, and there is no disadvantage of toxic gases without heating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112384112B_ABST
    Figure CN112384112B_ABST
Patent Text Reader

Abstract

The present invention provides a food contact component and a surface treatment method thereof which has antifouling, anticorrosion, wear resistance, antibacterial effects, etc. and does not worry about mixing foreign matter into food or generating toxic gas. The contact part of a metal or a food contact component containing metal is sprayed with roughly spherical fine particles of #220 to #800 (JIS R6001-1973) having a hardness equal to or higher than the surface hardness of the food contact component at a spray pressure of 0.2 MPa or more and collided with them, and a local and instantaneous temperature rise is generated at the collision part, so that the surface structure is refined, and a plurality of smooth arc-shaped recesses are formed on the entire surface of the above-mentioned food contact component, and then a powder composed of titanium or titanium alloy of #100 to #800 (JIS R6001-1973) is sprayed on the surface at a spray pressure of 0.2 MPa or more, so that titanium oxide that acts as a photocatalyst or semiconductor catalyst diffuses and penetrates near the surface of the contact surface with the above-mentioned food, thereby imparting antifouling, anticorrosion, wear resistance, and antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface treatment method, which is a surface treatment method for constituent components of a food manufacturing device or a food conveying device, a food weighing device, a food inspection device, or other various devices for processing food, such as constituent components that come into contact with food, or components that come into contact with food, such as packaging containers used for packaging food, cooking utensils for cooking food, etc. (in the present invention, these are collectively referred to as "food contact components"), and at least the portion that comes into contact with food.

[0002] Furthermore, the term "food" in the present invention includes all beverages and foods, and oral medications or supplements that are pharmaceuticals or quasi-drugs and food and drink all fall within the scope of the "food" described herein.

[0003] Furthermore, the "food" in the present invention includes not only the final food but also its raw materials and intermediate products. Background Art

[0004] As described above, in a food contact component having a surface in contact with food, in order to prevent food from adhering to the surface and to achieve anti-fouling or anti-corrosion, the portion in contact with food is formed of a fluororesin material or a fluororesin is coated on the surface of the portion in contact with food.

[0005] As an example, in Patent Document 1 disclosed below, it is proposed that in a food baking machine that bakes food such as meatballs to give food a color, a heat-resistant sheet belt is formed using a fluorine-based resin material, and the heat-resistant sheet belt is freely loaded and unloaded around the entire circumference of the surface of a food conveyor belt, and food is placed thereon.

[0006] Furthermore, Patent Document 2 disclosed below discloses a steel sheet coated with a fluororesin film used in food cooking utensils or heating cooking utensils such as baking pans for bread and cakes, frying pans, and rice cooker inner pots.

[0007] Prior art literature

[0008] Patent Literature

[0009] [Patent Document 1] Japanese Patent No. 5319008

[0010] [Patent document 2] Japanese Patent Application Publication No. 09-136382. Summary of the invention

[0011] [Problems to be solved by the invention]

[0012] Fluororesin has excellent water and oil repellency, as well as excellent chemical resistance, weather resistance, electrical insulation, wear resistance, etc. Therefore, by forming a food contact component using a fluorine-based resin material, or coating the surface of a food contact component with a fluorine-based resin, it is not only possible to make it difficult for dirt to adhere, but also to improve the weather resistance, corrosion resistance, and wear resistance of the food contact component.

[0013] However, due to the above-mentioned characteristics of fluororesins, fluororesin materials are difficult to process and have poor adhesion to other components. When a food contact component or a part thereof is to be formed using fluororesins, it is restricted by the processing method or installation structure.

[0014] In addition, in the structure of coating fluororesin, the coating film peels off from the surface of the food contact component over time and loses the above effect, so it is necessary to re-coat the fluororesin regularly or replace the component after the coating peels off. Therefore, not only is the maintenance more complicated, but there is also a concern that the peeled thin film will be mixed into the food as a foreign matter.

[0015] Furthermore, it has been reported that the gas generated when fluororesins are heated to a certain fixed temperature or above (315-375°C for polytetrafluoroethylene (PTFE), a representative fluororesin) is highly toxic. Therefore, the waste fluororesins that cannot be incinerated before re-coating need to be disposed of using a safe method, which not only increases the cost of disposal, but also cannot be used for food contact parts that are used at temperatures above the above temperature.

[0016] Furthermore, it has been reported that in a powder packaging machine for pharmaceuticals or the like, when a fluororesin is applied to a contact surface with the powder, the flowability of the powder is deteriorated due to the generation of static electricity.

[0017] Therefore, in recent years, there has been a tendency in the food processing industry to control the use of fluororesins in the above-mentioned food contact members that come into contact with food consumed by humans.

[0018] Furthermore, as a surface treatment method for the above-mentioned food contact components instead of fluororesin coating, for example, diamond-like carbon (DLC) coating is studied, but in the case of DLC coating, the cost increases significantly compared to the case of fluororesin coating. Therefore, a surface treatment method and food contact component are desired, which can replace the above-mentioned fluororesin at a lower cost through a relatively simple treatment, thereby giving the food contact component anti-adhesion of food or anti-fouling properties, corrosion resistance, wear resistance, antibacterial properties, etc.

[0019] Furthermore, even in the case of DLC coating, the coating is performed, and similarly to the case of fluororesin coating, there is a concern that flakes generated by peeling of the film may be mixed into food as foreign matter.

[0020] If it is desired to prevent foreign matter from being mixed into food due to the peeling of the coating film, a structure in which no coating film is provided on the surface of the food contact member is adopted. However, in this case, rust forms on the surface of the food contact member due to contact with moisture and salt contained in the food, so that not only is it easy for food or dirt to adhere to the rusted part, but there is also a concern that the deposited rust will peel off and mix into food as foreign matter.

[0021] Therefore, in a configuration in which a coating film is not formed on the surface of a food contact member, it is necessary to impart corrosion resistance and rust prevention properties by some method.

[0022] Therefore, the present invention is made to meet the above-mentioned expectations, and its purpose is to provide a food contact component and a surface treatment method thereof, which can be surface treated by relatively simple treatment and at low cost, and has no disadvantages such as foreign matter being mixed into food and toxic gas being generated by heating, etc., and can simultaneously impart antifouling properties, corrosion resistance, rust resistance, wear resistance, and antibacterial properties to the surface of the food contact component.

[0023] [Technical means to solve the problem]

[0024] To achieve the above object, the food contact component of the present invention is characterized in that:

[0025] The food contact member is made of metal or a material containing metal, and the structure of the contact surface with the food is miniaturized, and a plurality of smooth arc-shaped recesses without sharp protrusions are formed on the entire contact surface, and titanium oxide is diffused and infiltrated near the surface of the contact surface with the food (claim 1).

[0026] Alternatively, the surface layer containing the titanium oxide may have a thickness of about 0.5 μm, and may be activated and adsorbed on the micronized surface structure formed on the surface of the food contact member, and the titanium oxide may diffuse and penetrate from the surface of the substrate to a depth of about 5 μm inside (claim 2).

[0027] Alternatively, the titanium oxide diffused and permeated into the surface layer may have a gradient structure in which the amount of oxygen bound to the food contact member is greater near the surface and the amount of oxygen bound to the food contact member gradually decreases as it moves from the surface to the inside (claim 3).

[0028] To achieve the above-mentioned object, the surface treatment method of a food contact component of the present invention is characterized in that:

[0029] A transient heat treatment is performed, wherein the contact surface of a food contact member which is made of metal or a material containing metal and has a surface in contact with food is sprayed with approximately spherical fine particles of #220 to #800 (JIS R6001-1973) having a hardness equal to or higher than that of the contact surface of the food contact member at a spray pressure of 0.2 MPa or more and caused to collide with each other, thereby causing a local and transient temperature rise at the collision portion; the structure of the contact surface of the food contact member which is in contact with food is miniaturized, and a plurality of smooth arc-shaped recesses without sharp protrusions are formed on the entire contact surface with the food.

[0030] The contact surface of the food contact component subjected to the instantaneous heat treatment is sprayed with a powder composed of titanium or titanium alloy of #100 to #800 (JIS R6001-1973) at a spray pressure of 0.2 MPa or more, so that titanium oxide diffuses and penetrates near the surface of the contact surface with the food (claim 4).

[0031] A pretreatment step may also be performed, in which the carbide powder of #220 to #800 (JIS R6001-1973) is sprayed at a spray pressure of 0.2 MPa or more on at least the portion of the food contact component that contacts the food before the instantaneous heat treatment, so that the carbon element in the carbide powder is diffused to the surface of the food contact component (claim 5).

[0032] The carbide powder sprayed in the pretreatment step is preferably silicon carbide, more preferably SiCα (claim 6).

[0033] [Effects of the Invention]

[0034] According to the above-described configuration of the present invention, and according to the food contact member and the surface treatment method thereof of the present invention, the following remarkable effects can be obtained.

[0035] In the food contact component surface treated by the method of the present invention, a relatively simple method of spraying two kinds of particles can be used to form a surface on the food contact component that is difficult for food and dirt to adhere to, has excellent wear resistance and corrosion resistance, and exhibits antibacterial effects.

[0036] Furthermore, the following food contact component and food contact component surface treatment method can be provided. In the surface treatment method of the present invention, the above-mentioned effect can be imparted to the food contact component by a relatively simple operation of spraying particles. Therefore, not only can the surface treatment be performed within a short delivery period, but also, unlike fluororesin coating, antifouling and the like are not achieved by forming a coating film, but the above-mentioned effect is achieved by the refinement of the surface structure and the formation of arc-shaped recesses based on the above-mentioned instantaneous heat treatment, and the diffusion and penetration of titanium oxide based on the spraying of titanium powder. Therefore, the effect of the surface treatment will not be lost due to peeling of the coating film, and there is no concern that thin pieces of the peeled coating film will be mixed into food as foreign matter.

[0037] Furthermore, in the food contact component surface-treated by the method of the present invention, not only is there no concern about the generation of toxic gases due to heating as in the case of fluororesin coating, but the titanium oxide diffused and permeated to the surface of the food contact component also acts as a photocatalyst or semiconductor catalyst. In particular, because the catalyst is more activated under heating, not only can the corrosion resistance and rust prevention effect brought about by the reducing action of the catalyst be obtained, but also the deodorizing or odor-proofing, decomposition of toxic gases, antibacterial and antifungal effects, etc., which are suitable for machinery or equipment in contact with food, can be exerted.

[0038] Furthermore, when a pretreatment step is performed in which a specific carbide powder, such as silicon carbide (SiC), preferably SiCα powder, is sprayed onto the surface of the food contact component before the instantaneous heat treatment, the hardness near the surface can be further increased by diffusing and penetrating the carbon in the carbide powder into the surface of the food contact component, and the wear resistance can be further improved, thereby achieving the effect obtained by the above-mentioned surface treatment for a longer period of time. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a photograph of the surface state of the test piece (untreated) after the CASS test.

[0040] Figure 2 This is a photograph of the surface state of the test piece (Example) after the CASS test. DETAILED DESCRIPTION

[0041] Hereinafter, the surface treatment method of the food contact member of the present invention will be described.

[0042] [Treatment object: Food contact parts]

[0043] Regarding the surface treatment method of the present invention, among the components of food manufacturing devices or food conveying devices, food measuring devices, food inspection devices, or other various food processing devices, the components that come into contact with food, such as the inner surface of the funnel or flow channel arranged in these devices, the outer periphery of the rolling roller used to stretch snacks or raw dough, the surface of the tray or metal mesh for carrying food, the molding surface of the mold for molding food, the packaging container (such as a can) used for packaging food, the cooking utensils such as a frying pan or pot, etc., which have a surface that comes into contact with food, all meet the food contact components described in the present invention.

[0044] The material of the food contact component to be treated is not particularly limited as long as it contains metal. As an example, various steel materials such as stainless steel (SUS material), carbon tool steel (SK material), alloy tool steel (SKS, SKD, SKT material) can be treated by the present invention. In addition to steel materials such as high-speed tool steel (SKH material), food contact components made of various materials such as sintered metals such as superhard alloys, Cu-Be alloys, and other non-ferrous metal alloys can also be treated.

[0045] Furthermore, the food contact member may not necessarily be entirely formed of a metal material, but may partially contain other components such as ceramics.

[0046] [Surface treatment]

[0047] The surface treatment of the present invention described below is performed on at least the surface of the portion of the food contact member described above that comes into contact with food.

[0048] (1) Preprocessing steps

[0049] This step (pretreatment step) is a step performed as needed, and is not necessarily required depending on the use of the food contact member, and is not an essential step in the present invention.

[0050] In this step, carbide powder is dry-sprayed onto the surface of the food contact component to be processed, and the surface is adjusted, for example, a discharge hardened layer or softened layer generated on the surface by discharge machining or cutting during the manufacture of the food contact component is removed, or directional processing marks (cutting marks, grinding marks, knife marks, etc.) generated during cutting, grinding and polishing are removed, and the carbon element in the carbide powder is diffused and penetrated into the surface of the food contact component to perform carburizing at room temperature.

[0051] As the carbide powder to be used, for example, powders of carbides such as B4C, SiC (SiC(α)), TiC, VC, graphite, and diamond can be used. Preferably, SiC is used, and more preferably, SiC(α) is used.

[0052] Regarding the carbide powder used, when the purpose is to remove the discharge hardened layer or softened layer or to remove directional processing marks, it is preferred to grind the fired carbide-based ceramics and use the polygonal powder obtained by screening to exert a higher cutting force. When the purpose is not such cutting, the shape of the carbide powder is not particularly limited, and spherical and other various shapes can be used.

[0053] Regarding the size of the powder used, in order to obtain the injection speed required to achieve diffusion and penetration of the carbon element, #220 (JIS R6001-1973) (less than 105 μm to 44 μm) to #800 (JIS R6001-1973) (average value of average diameter is 22 μm to 18 μm) is used, and it is preferred to use #240 (JIS R6001-1973) (average value of average diameter is 87.5 μm to 73.5 μm) or a smaller particle size (larger particle size number (#)) so-called "fine powder".

[0054] As a method of spraying such carbide powder onto the surface of the food contact member, any known various spraying devices can be used as long as they can spray the powder in a dry manner. However, an air spraying device is preferably used because the spraying speed and spraying pressure can be relatively easily adjusted.

[0055] As such air blasting processing devices, there are various devices such as direct pressure type, suction type, gravity type, or other blasting devices, and any one of them can be used. As long as it has the performance of dry blasting with a blasting pressure of 0.2 MPa or more, there is no particular limitation on its model, etc.

[0056] If the above-mentioned carbide powder is sprayed dry-type at high speed on the surface of the food contact component in contact with food using the above-mentioned spraying device, the discharge hardened layer or softened layer caused by discharge machining or cutting during the manufacture of the food contact component, directional processing marks, etc. are removed, and the surface of the food contact component is adjusted to be non-directional.

[0057] In addition, due to the collision between the carbide powder and the surface of the food contact component, the temperature of the surface of the food contact component at the portion where the carbide powder collides is locally increased, and the carbide powder is also heated and thermally decomposed. The carbon element in the carbide of the above-mentioned carbide powder diffuses and penetrates into the surface of the food contact component, thereby increasing the carbon amount in this portion, which can greatly improve the hardness of the surface of the food contact component after the pretreatment step.

[0058] Thus, in the present invention, as the above-mentioned pretreatment, carburizing treatment is performed by causing the carbide powder to collide with the food contact member by blasting, thereby causing thermal decomposition due to the increase in temperature of the carbide powder, and diffusing and penetrating the carbon element in the carbide powder generated by the decomposition into the surface of the food contact member.

[0059] According to the pretreatment performed using this method, the diffusion and penetration of carbon elements into the food contact component has a gradient structure, that is, it is most significant near the surface and the increased carbon amount is also relatively large. Therefore, the amount of carbon increased by the above-mentioned diffusion into the interior of the food contact component gradually decreases as the carbon amount at this depth is farther from the surface (deeper), and at a certain depth the carbon amount is reduced to the untreated state.

[0060] Furthermore, although the temperature of the carbide powder and the food contact component locally rises when the above-mentioned carbide powder collides with the surface of the food contact component, the temperature rise is local and instantaneous, so there will be no deformation or phase change of the food contact component caused by heat treatment in a general carburizing treatment such as heating the entire food contact component in a carburizing furnace. In addition, since fine carbides are produced, the close contact strength is high and no carburized abnormal layer is produced.

[0061] (2) Instantaneous heat treatment step

[0062] In this step (instantaneous heat treatment step), spherical powder is dry-sprayed onto the surface of at least the portion of the food contact member to be treated that contacts the food (when the above-mentioned pretreatment step is performed, the surface after the pretreatment step), so that countless arc-shaped tiny recesses are formed on the surface of the food contact member, and the structure near the surface of the food contact member is miniaturized, thereby seeking to further improve the surface hardness.

[0063] The material of the spherical powder used is not particularly limited as long as it has a hardness equal to or higher than that of the food contact component to be treated. For example, in addition to various metal powders, ceramic powders can also be used, and powders of the same material as the above-mentioned carbide powder (carbide) can also be used.

[0064] The spherical powder is spherical and can form numerous arc-shaped minute recesses on the surface of the food contact member as described above.

[0065] Furthermore, the so-called "spherical shape" in the present invention does not necessarily mean a "sphere" strictly, but also includes a shape similar to a sphere without corners.

[0066] Such spherical powders can be obtained, for example, by atomization for metal materials and by melting after pulverization for ceramic materials.

[0067] As the particle size of the powder to be used, in order to obtain the spraying speed required for plastically deforming the surface of the food contact member by collision to form a semicircular concave portion (pit), #220 (JIS R6001-1973) (105 μm or less to 44 μm) to #800 (JIS R6001-1973) (average value of average diameter is 22 μm to 18 μm) are used, and it is preferred to use #240 (JIS R6001-1973) (average value of average diameter is 87.5 μm to 73.5 μm) or so-called "fine powder" having a smaller particle size (larger particle size number (#)).

[0068] In addition, as a method for spraying such spherical powder onto the surface of the food contact member, as described in the description of the pretreatment step as a method for spraying carbide powder, various known spraying devices can be used as long as they can perform dry spraying, and their models are not particularly limited as long as they have the performance of being able to spray at a spray pressure of 0.2 MPa or more.

[0069] When the spherical powder as described above is sprayed onto the contact surface of the food contact member with the food, the collision of the spherical powder causes plastic deformation in the portion of the surface of the food contact member that collides with the spherical powder.

[0070] As a result, even in the case of a pretreatment step using a polygonal carbide powder, and even in the case of a situation where sharp-shaped peaks are formed on the surface of the food contact member due to cutting caused by collision with the carbide powder, the sharp peaks are crushed to form countless smooth arc-shaped recesses (pits) irregularly on the entire surface of the food contact member, thereby improving the surface roughness.

[0071] Furthermore, it is considered that the effect obtained by utilizing the so-called "shot peening method" is also simultaneously imparted, that is, by the heat generated during the collision with the spherical powder, an instantaneous heat treatment is performed in which local heating and cooling are instantaneously generated at the collision portion, and by the plastic deformation during the formation of the arc-shaped recess, the surface of the food contact component is microcrystallized and work hardened, and the surface hardness of the food contact component is further improved compared to the state after the pretreatment step, and compressive residual stress is imparted due to the plastic deformation of the surface, thereby improving the fatigue strength of the food contact component.

[0072] (3) Spraying of titanium powder

[0073] Titanium or titanium alloy powder (hereinafter collectively referred to as "titanium powder") is further sprayed on at least the food contact surface of the food contact member subjected to the instantaneous heat treatment as described above, so that titanium oxide diffuses and permeates the surface of the food contact member.

[0074] The shape of the titanium powder is not particularly limited as long as it is #100 (JIS R6001-1973) (210 μm or less to 74 μm) to #800 (JIS R6001-1973) (average diameter of 22 μm to 18 μm), and spherical, polygonal, and other various shapes can be used.

[0075] Furthermore, a powder of a noble metal (such as Au, Ag, Pt, Pd, and Ru) having the effect of promoting the catalytic function of titanium oxide may be mixed in an amount within a range of about 0.1 to 10% by weight relative to the titanium powder and sprayed.

[0076] In the following description, when the noble metal powder and the titanium powder are not particularly described separately, the titanium powder mixed with the noble metal is also included and is collectively referred to as the titanium powder.

[0077] Thus, when titanium powder mixed with precious metal powder is sprayed, the particle sizes of the two powders do not necessarily have to be the same, and titanium powder and precious metal powder having different particle sizes may be used.

[0078] In particular, since the specific gravity of precious metal powder is greater than that of titanium powder, the following adjustment can be made: the particle size of the metal powder is smaller than that of the titanium powder to make the weights of the two powders close to each other, thereby making the injection speed of the two powders approximately the same.

[0079] As a method for spraying the titanium powder described above onto the surface of the food contact component, similar to the case described as the spraying method of carbide powder or spherical fine particles in the description of the pretreatment step and the instantaneous heat treatment step, various known spraying devices can be used as long as they can perform dry spraying, and there is no particular limitation on the model, etc. as long as they have the performance of spraying at a spray pressure of 0.2 MPa or more.

[0080] If the titanium powder described above is sprayed onto the surface of a food contact component having a surface microcrystallized by an instantaneous heat treatment step and caused to collide, the speed of the titanium powder changes before and after the collision, and the energy corresponding to the decreased speed becomes thermal energy that locally heats the collision portion.

[0081] The titanium powder constituting the spray powder is heated on the surface of the food contact component by this thermal energy, so that the titanium is activated and adsorbed on the surface of the food contact component and diffuses and penetrates. At this time, the surface of the titanium reacts with the oxygen in the compressed gas or the oxygen in the atmosphere and oxidizes, forming a surface layer on the surface of the food contact component that includes the base material and titanium oxide (TiO2) diffused and penetrated into the base material.

[0082] The thickness of the surface layer containing titanium oxide is about 0.5 μm, and it is activated and adsorbed on the miniaturized surface structure formed on the surface of the food contact component by instantaneous heat treatment. The oxidized titanium (titanium oxide and precious metal when containing precious metal powder) diffuses and penetrates from the surface of the substrate to a depth of about 5 μm inside.

[0083] Furthermore, the titanium diffused and penetrated into the surface layer thus formed is oxidized by reacting with oxygen in compressed gas or the atmosphere due to the heat generated during collision, and therefore has a gradient structure in which the amount of oxygen bound to it is greater near the surface with the highest temperature, and the amount of oxygen bound to it gradually decreases as it moves from the surface to the inside.

[0084] [Example]

[0085] Test Example 1 shows the results of a corrosion resistance evaluation test on a test piece of a food contact component of the present invention, Test Example 2 shows the results of an antibacterial test on a test piece subjected to the surface treatment of the present invention, and Test Examples 3 to 7 show examples of application to food contact components for various foods.

[0086] [Test Example 1] Corrosion resistance test

[0087] (1) Purpose of the test

[0088] It was confirmed that the food contact component of the present invention also exhibits an anti-corrosion effect in an environment where it is not irradiated with light.

[0089] (2) Test methods

[0090] A test piece susceptible to stress corrosion cracking was prepared by welding (TIG welding) SUS304 and imparting tensile residual stress. The CASS test was performed on the welded but untreated test piece and the welded food contact member of the present invention (surface treated by instantaneous heat treatment + titanium powder spraying) according to "7.3 CASS test method" of JIS H 8502:1999.

[0091] Unlike the salt water test, which is performed by simply spraying salt water, the CASS test performed here is a corrosion resistance test in which copper chloride and acetic acid are added to salt water and the acidity is adjusted to pH 3.0 to 3.2, and is a corrosion resistance test performed in an extremely severe corrosive environment.

[0092] In addition, the test conditions of the CASS test are shown in Table 1 below.

[0093] [Table 1]

[0094] CASS test conditions

[0095] project When adjusting Under test Sodium chloride concentration g / l 50±5 50±5 <![CDATA[Concentration of copper chloride (CuCl2, H20) g / l]]> 0.26±0.02 - pH 3.0 3.0~3.2 <![CDATA[Spray volume ml / 80cm 2 / h]]> - 1.5±0.5 Test tank temperature ℃ - 50±2 Brine tank temperature ℃ - 50±2 Air saturator temperature ℃ - 63±2 Compressed air pressure kPa - 70~167

[0096] (3) Test results and analysis

[0097] At Figure 1 (unprocessed) and Figure 2 (Example) The state of the test piece after the CASS test is shown.

[0098] like Figure 1 As shown, red rust was confirmed to be generated on the surface of the untreated test piece.

[0099] On the other hand, in the test piece of the food contact member of the present invention, Figure 2 As shown, no rust was observed, and the clean state before the CASS test was maintained. In the above test piece, it was confirmed that extremely high corrosion resistance was obtained.

[0100] Here, it is known that the shot peening method has the effect of releasing the tensile residual stress generated in the test piece during welding and imparting compressive residual stress, and therefore has the effect of preventing stress corrosion cracking, but does not prevent the occurrence of corrosion (rust) itself.

[0101] Thus, in the test piece of the food contact component of the present invention, it is believed that the rust prevention effect is not so much the effect of instantaneous heat treatment by spraying spherical fine particles, but rather the effect of the titanium oxide film formed on the surface by spraying titanium powder acting as a photocatalyst or semiconductor catalyst (reducing property).

[0102] In the CASS test, the test was performed using a test tank with a cover in order to maintain the environment in the test tank in a fixed state. Therefore, the test piece was not irradiated with light during the test.

[0103] On the other hand, in the CASS test, the temperature in the test tank is set to 50±2°C, so the temperature of the test piece is also heated to 50±2°C. It is believed that by conducting the test in this heated state, the titanium oxide film acts as a photocatalyst or semiconductor catalyst.

[0104] Thus, although it is not clear why it functions as a photocatalyst in an environment without light irradiation, industrially produced titanium oxide loses oxygen when heated at high temperatures, changing from white to black, and this black color shows semiconductor properties. That is, when it becomes a state lacking oxygen bonding, it shows semiconductor properties.

[0105] As described above, the titanium oxide diffused and infiltrated into the surface of the food contact member using the method of the present invention has a gradient structure, in which the amount of oxygen bonded to the food contact member is the largest near the surface of the food contact member, and the amount of oxygen bonded to the food contact member gradually decreases as it moves from the surface to the inside. Therefore, it is believed that the titanium oxide present in the inside lacks bonding with oxygen and has properties as a semiconductor.

[0106] Therefore, it is considered that the catalyst functions as a catalyst (referred to as a "semiconductor catalyst" in this specification) that causes charge transfer due to thermal excitation and thus brings about a charge transfer type redox effect when used under heating.

[0107] Generally speaking, semiconductor catalysts must be catalysts with special structures, such as those doped with electron-releasing elements or electron-accepting elements. However, the titanium oxide film obtained by a relatively simple method of spraying titanium powder has a catalytic effect due to heat that far exceeds expectations.

[0108] Furthermore, the surface roughness Ra of the smooth part near the welding part of the test piece after instantaneous heat treatment by spraying #400 (diameter 53μm to 30μm) high-speed steel fine particles at a spray pressure of 0.5MPa was 0.3μm, and the surface hardness was increased from 300Hv in the untreated state to 580Hv.

[0109] On the other hand, in the smooth portion of the test piece of the embodiment of the present invention which was subjected to instantaneous heat treatment under the above conditions and then sprayed with titanium powder having a particle size of 150μm to 45μm at a spray pressure of 0.4MPa, the surface roughness Ra was improved to 0.2μm. On the other hand, the surface hardness after treatment remained at 580Hv and did not change.

[0110] Here, the hardness of titanium is about 300 Hv, but the hardness of titanium oxide (TiO2) as titanium oxide reaches 1000 Hv. Therefore, the surface hardness of the titanium powder used for spraying is also formed through the formation of an oxide film, becoming a higher hardness of about 1000 Hv than the surface hardness of the test piece after instantaneous heat treatment, which is 580 Hv.

[0111] Therefore, in the surface treatment method of the present invention, it is considered to perform calendering to crush and smooth the top ends of the convex parts of the surface irregularities formed by collision with fine particles during the instantaneous heat treatment by spraying titanium powder on the surface after the instantaneous heat treatment.

[0112] That is, the surface of the test piece after the instantaneous heat treatment is in a state where not only recesses (pits) formed by the collision of fine particles but also sharp protrusions are formed between the formed recesses.

[0113] In this regard, by further spraying titanium powder on the surface after the instantaneous heat treatment, the convex and concave parts formed on the surface are crushed and smoothed (calendered), thereby converting them into smooth-shaped concave parts without sharp convex parts. It is believed that this will reduce the value of the surface roughness Ra as mentioned above.

[0114] Thus, in the surface treatment method of the food contact component of the present invention, it is considered that the structure will be changed to the following: the depressions (small pits) generated by the instantaneous heat treatment are retained, the contact area with the food is reduced and it is difficult for food to adhere to it. In addition, the top of the sharp protrusion that becomes a resistance when in contact with the food is crushed and smoothed, and the photocatalyst or semiconductor catalyst effect of titanium oxide is used to prevent fouling and corrosion. As a result, not only the effect of preventing food from adhering to it is improved, but the processed surface itself is also excellent in that it is difficult for food to adhere to it.

[0115] [Test Example 2] Antibacterial Test

[0116] (1) Purpose of the test

[0117] It was confirmed that the food contact member of the present invention exhibits an antimicrobial effect.

[0118] (2) Test methods

[0119] The test piece of the food contact component of the present invention and the untreated test piece are placed in sterile culture dishes, respectively, and 0.3 mL of the inoculation bacterial solution of Legionella (Legionella pneumophila) which causes bacterial infection is inoculated on the test surface, and after covering it with a coating film, it is irradiated with a black light under the conditions of 40°C and a relative humidity of 90% or more and allowed to contact for 1 to 3 hours. After 1 hour and 3 hours, the test bacterial solution attached to the specimen and the coating film is washed out using a sterile phosphate buffer solution into other sterile culture dishes.

[0120] The washed bacterial solution was cultured at 35°C for 5 days using Legionella MWY agar medium (Kanto Chemical Co., Ltd.), and the bacterial count was determined. The test results are shown in Table 2 below.

[0121] [Table 2]

[0122] Results of antibacterial test against Legionella (in cfu / mL)

[0123]

[0124] (3) Test results and analysis

[0125] In the untreated test piece, the number of Legionella bacteria did not decrease at all after 60 minutes, and the number of decreases was small even after 180 minutes.

[0126] On the other hand, in the test piece of the food contact member of the present invention, the number of Legionella bacteria was reduced to less than half after 60 minutes and was reduced to an undetectable state after 180 minutes, confirming a high antibacterial effect.

[0127] In addition, since such a high antibacterial effect was exerted, it was confirmed that the titanium oxide diffused and permeated into the surface of the test piece by the sprayed titanium powder acted as a photocatalyst or a semiconductor catalyst.

[0128] Furthermore, although details are omitted, it can be confirmed through experiments that, by performing surface treatment using the method of the present invention, antibacterial properties against Staphylococcus aureus or Escherichia coli in addition to the Legionella bacteria disclosed above can be obtained.

[0129] Thus, by performing the surface treatment using the method of the present invention, high antimicrobial properties are imparted, and therefore the surface treatment of the present invention can be said to be suitable for the surface treatment of food contact members that come into contact with foods.

[0130] [Test Example 3] Processing example of drying net for dried fruit production

[0131] (1) Processing conditions

[0132] A metal drying net (SUS304) used for placing and drying sliced ​​fruit pulp during the production of dried fruit (mango) was used as a food contact member, and the drying net was subjected to the surface treatment of the present invention under the conditions shown in Table 3 below (Example 1).

[0133] As comparative examples, a fluororesin-coated drying web (Comparative Example 1) and an untreated drying web (Comparative Example 2) were used.

[0134] [Table 3]

[0135] Processing conditions of drying net (SUS304) for dried fruit manufacturing

[0136]

[0137]

[0138] (2) Test methods and test results

[0139] Dried fruit (mango) was produced using a drying net surface-treated by the method of the present invention (Example 1), a drying net coated with a fluororesin (Comparative Example 1), and an untreated drying net (Comparative Example 2).

[0140] Mango slices with a thickness of 5 mm were placed on the drying nets of Example 1 and Comparative Examples 1 and 2 respectively in a drying oven (dark room), and hot air from a heater was introduced into the drying oven for 24 hours to dry the mango slices. The peelability of the dried fruit when it was recovered and the state of dirt on the drying net after peeling were observed. The results are shown in Table 4.

[0141] [Table 4]

[0142] Test results of drying nets for drying dried fruits

[0143]

[0144] (3) Analysis, etc.

[0145] In the drying net coated with fluororesin (Comparative Example 1), there were few problems such as adhesion and peeling failure of fructose, but the fluororesin had to be re-coated approximately every month due to peeling of the coating film.

[0146] In addition, since there is a concern that a portion of the peeled coating may be mixed into food as foreign matter, the use of fluororesin-coated products has been discontinued in recent years, and untreated drying nets have been used instead (Comparative Example 2).

[0147] However, when the untreated drying net (Comparative Example 2) is used, the drying net becomes noticeably dirty after use due to dirt caused by the adhesion of the fruit sugar and the adhesion of the fruit pulp due to poor peeling. Each time the untreated drying net (Comparative Example 2) is used, it needs to be cleaned with a detergent and a brush, and the cleaning after use requires a lot of labor and time, and the cleaning requires a lot of water, so the treatment after use costs a lot of money.

[0148] On the other hand, in the drying web surface treated by the method of the present invention (Example 1), similarly to the case of fluororesin coating, no fructose adhered, no peeling failure was observed, and no adhesion of dirt was visually confirmed after use.

[0149] In addition, by spraying titanium powder, an antibacterial effect is also exerted in the dry net (Example 1) surface-treated by the method of the present invention (refer to the "[Test Example 2] Antibacterial Test" column disclosed above), so after use, it can be reused by simply washing with water. In addition, the effect of the surface treatment lasts even after 1 month, so there is no need to perform surface treatment again.

[0150] Regarding this effect in the drying net (Example 1) surface-treated by the method of the present invention, it is believed that the contact area between the surface of the wire material constituting the drying net and the pulp is reduced by forming pits by instantaneous heat treatment, and the surface structure of the wire material is refined and hardened by instantaneous heat treatment, and the wear resistance is improved, resulting in that the effect of the surface treatment lasts for a long time. In addition, by spraying titanium powder, titanium oxide is diffused and penetrated into the surface of the wire material, and titanium oxide acts as a photocatalyst or semiconductor catalyst, thereby making it difficult for dirt to adhere and decomposing the attached dirt, thereby obtaining the above-mentioned effect.

[0151] Furthermore, in this test, the dried fruit was produced in a dark drying oven as described above, so it is believed that, as in the above-mentioned corrosion resistance test (Test Example 1), antifouling or good peeling properties are obtained by activating the catalyst function using heat.

[0152] In addition, in the drying net (Example 1) surface-treated by the method of the present invention, the effect of eliminating the deflection of the metal wire net was also confirmed.

[0153] [Test Example 4] Processing Example of Food Inserting Funnel

[0154] (1) Processing conditions

[0155] A food material input funnel (lower end outlet diameter 30 mm, upper end inlet diameter 140 mm, height 270 mm) installed in a food manufacturing device was used as a food contact member, and the entire inner surface and a portion of the outer surface (range 30 mm from the lower end outlet height) of the funnel were surface treated by the method of the present invention under the conditions shown in Table 5 below (Example 2).

[0156] As a comparative example, an untreated funnel was used (Comparative Example 3).

[0157] [Table 5]

[0158] Processing conditions of food feeding funnel (SUS316)

[0159]

[0160]

[0161] (2) Test methods and test results

[0162] The funnel surface treated by the method of the present invention (Example 2) and the untreated funnel (Comparative Example 3) were used to put food into the funnel, and the adhesion state of the food and the corrosion state caused by the salt and water of the food were observed. The replacement period (lifespan) was evaluated when the sealing part between the lower end outlet of the funnel and the pipe connected to the lower end outlet was poorly sealed due to corrosion and adhesion of food. The results are shown in Table 6.

[0163] [Table 6]

[0164] Test results of food feeding funnel

[0165]

[0166] (3) Analysis, etc.

[0167] As a food material input funnel, a funnel with a fluorine resin coating on the surface is generally used, but due to the problem of foreign matter mixing into food, an untreated funnel is used instead (Comparative Example 3).

[0168] However, when an untreated funnel (Comparative Example 3) is used, corrosion occurs in a relatively short period of time due to the salt and moisture contained in the food, and the food adheres to the sealing portion of the lower outlet of the funnel and the pipe connected to the lower outlet, resulting in poor sealing, and the funnel needs to be replaced with a new one approximately every 3 months.

[0169] In contrast, in the funnel (Example 2) that has been surface treated using the treatment method of the present invention, not only is it difficult for food to adhere to the surface-treated portion, but as described above, titanium oxide is diffused and penetrated into the surface by the spraying of titanium powder to act as a photocatalyst or semiconductor catalyst. As a result, oxidation (corrosion) is difficult to occur due to its reducing properties, and corrosion of the sealing portion can be prevented.

[0170] As a result, the funnel treated by the method of the present invention (Example 2) exhibited good sealing properties for a long time and could be used for about 1 year without replacement, which was 4 times that of the untreated funnel (Comparative Example 3).

[0171] Furthermore, when an untreated funnel (Comparative Example 3) was used, the metallic smell of the funnel was sometimes transferred to food. However, when a funnel surface-treated by the method of the present invention was used (Example 2), the metallic smell was less likely to be transferred to food.

[0172] Regarding this effect, as can be seen from the CASS test results shown in the previous "[Test Example 1] Corrosion Resistance Test" column, the corrosion resistance is improved by the catalytic action obtained by the diffusion and penetration of titanium oxide, thereby inhibiting the elution of metal components into food, and the odor components are decomposed by the catalytic action, thereby better preventing the transfer of metallic odor to food.

[0173] [Test Example 5] Processing Example of the Rotor of a Quantitative Powder Packaging Machine

[0174] (1) Processing conditions

[0175] A metering rotor (a turbine mold having 10 plate-shaped blades radially welded to a hub, which delivers the metered powder accumulated between the blades to a packaging step while rotating, thereby achieving quantitative supply) provided in a packaging machine used for quantitative packaging of edible powder was used as a food contact member. The entire surface of the rotor was pre-treated by spraying SiC powder #400 (JIS R6001-1973) (average diameter of 44 μm to 37 μm) for about 10 minutes, and then surface-treated according to the method of the present invention under the conditions shown in Table 7 below (Example 3).

[0176] As a comparative example, a rotor that had been polished and ground was used (Comparative Example 4).

[0177] [Table 7]

[0178] Processing conditions of rotor (SUS304) for quantitative powder packaging machinery

[0179]

[0180]

[0181] (2) Test methods and test results

[0182] The rotor surface treated by the method of the present invention (Example 3) and the rotor polished (Comparative Example 4) were installed in a quantitative powder packaging machine to carry out quantitative powder packaging. The adhesion of the powder to the rotor and the state of corrosion were visually confirmed, and the replacement period was evaluated as "life". The results are shown in Table 8.

[0183] [Table 8]

[0184] Test results of rotors for quantitative powder packaging machinery

[0185]

[0186] (3) Analysis, etc.

[0187] The rotor that has been polished and ground (Comparison Example 4) is finished by professional grinding, so it is more expensive than the rotor that has been surface treated using the method of the present invention (Example 3) and takes a longer time to deliver. However, in the rotor that has been polished and ground (Comparison Example 4), rust occurs on the welding part in a shorter period of time and needs to be replaced within about 3 months.

[0188] In addition, the powder adheres to the surface of the blades or the hub, and the amount of the powder adhered varies depending on the moisture absorption state of the powder. Therefore, the measurement error is not fixed due to the influence of the use environment, so in order to accurately measure, fine adjustments are required each time.

[0189] In contrast, in the rotor (Example 3) that has been surface treated using the method of the present invention, not only can low cost and short delivery be achieved, but rust will not form on any part including the welded portion, and no powder will adhere to the surface, so a certain amount of powder can be accurately measured without the need for fine-tuning.

[0190] Furthermore, in the rotor that has been surface treated using the method of the present invention (Example 3), the wear resistance and the like are also improved due to the high hardness of the surface, so the above-mentioned effects are maintained for a long time, and the replacement period can be extended to about 6 months. Compared with the rotor that has been polished and ground (Comparison Example 4), the life is extended to 2 times.

[0191] [Test Example 6] Piercing rod of wheat flour bag opener

[0192] (1) Processing conditions

[0193] A piercing rod provided in an opener for a flour bag was used as a food contact member. The opener for a flour bag was used to place a bag containing flour in a funnel, pierce the bag with the piercing rod to open the bag, and take the flour in the bag into the funnel. The outer surface of the piercing rod was pre-treated by spraying SiC powder #400 (JIS R6001-1973) (average diameter of 44 μm to 37 μm) for about 1 minute, and then surface treatment according to the method of the present invention was performed under the conditions shown in Table 9 below (Example 4).

[0194] As a comparative example, a puncture rod whose outer surface was coated with fluororesin was used (Comparative Example 5).

[0195] [Table 9]

[0196] Processing conditions of the piercing rod (SUS40C) for wheat flour bag opener

[0197]

[0198] (2) Test methods and test results

[0199] The piercing rod surface treated by the method of the present invention (Example 4) and the piercing rod coated with fluororesin (Comparative Example 5) were respectively attached to the flour bag opener and pierced the flour bag, and the adhesion state and wear state of the flour on the outer surface of the piercing rod were visually confirmed, and the replacement period was evaluated as "life". The results are shown in Table 10.

[0200] [Table 10]

[0201] Test results of the piercing rod of the wheat flour bag opener

[0202]

[0203] (3) Analysis, etc.

[0204] Since the piercing rod needs to be strong, SUS440C is used. However, in the piercing rod coated with fluororesin (Comparative Example 5), although wheat flour can be prevented from adhering to the surface, the fluororesin coating peels off due to wear within about 3 months, and corrosion occurs in the base material due to the peeling of the fluororesin coating.

[0205] In contrast, in the piercing rod surface-treated by the method of the present invention (Example 4), although the effect of preventing wheat flour from adhering to the surface is obtained similar to that of the piercing rod coated with fluororesin (Comparative Example 5), in the piercing rod surface-treated by the method of the present invention (Example 4), wheat flour is difficult to adhere even when the humidity is high.

[0206] This is considered to be because the titanium oxide diffuses and permeates to exert a catalytic effect, thereby decomposing water and deposits on the surface of the puncture rod.

[0207] Furthermore, in the puncture rod coated with fluororesin (Comparative Example 5), the fluororesin coating was worn and peeled off within about 3 months as described above, thereby losing the effect of preventing wheat flour adhesion, etc., and it became necessary to replace it. However, in the puncture rod surface-treated by the method of the present invention (Example 4), the effects of preventing wheat flour adhesion and rust prevention were maintained for about 6 months, which is twice as long as that of Comparative Example 5.

[0208] [Test Example 7] Forming Punch for Tablet Manufacturing Device

[0209] (1) Processing conditions

[0210] A punch plated with hard chromium is used as a food contact component. The punch is set in a tablet manufacturing device for manufacturing tablets as pharmaceuticals and is used together with a molding die when compressing drug powder into tablets. The surface of the punch is surface treated based on the method of the present invention under the conditions shown in Table 11 below (Example 5).

[0211] As a comparative example, a punch was used in a state where the hard chrome plating was maintained (Comparative Example 6).

[0212] [Table 11]

[0213] Processing conditions of the forming punch (SKD-11 chrome-plated product) for tablet manufacturing equipment

[0214]

[0215] (2) Test methods and test results

[0216] The punches surface-treated by the method of the present invention (Example 5) and the untreated punches in the chrome-plated state (Comparative Example 6) were respectively installed in a tablet manufacturing device, and the powder was compressed to manufacture tablets. The adhesion state and wear state of the powder were visually confirmed, and the replacement period was evaluated as "life". The results are shown in Table 12.

[0217] [Table 12]

[0218] Test results of the forming punch of the tablet manufacturing device

[0219]

[0220] (3) Analysis, etc.

[0221] Generally, there are a plurality of network cracks on the surface of the hard chrome plated film, and in the punch (Comparative Example 6) which is still hard chrome plated, powder adheres to the cracked portions, and wear occurs from these portions as starting points.

[0222] On the other hand, in the punch surface-treated by the method of the present invention (Example 5), the cracks existing in the hard chrome plating disappeared, and as a result, it was possible to prevent the powder from adhering to the cracked portion and the wear from occurring starting from the crack.

[0223] Furthermore, in the punch (Example 5) surface-treated by the method of the present invention, it is considered that the surface hardness is also increased, and this, combined with the disappearance of the above-mentioned cracks, significantly improves the wear resistance.

[0224] Furthermore, chromium and titanium are a combination of metals that are easy to migrate or melt into each other, and the hard chromium-plated surface is easy to produce activated adsorption and diffusion penetration of titanium oxide. Therefore, it is believed that the corrosion resistance of the punch is improved through the role of titanium oxide as a photocatalyst or semiconductor catalyst, and dirt is difficult to adhere to, and the attached dirt is easy to decompose.

[0225] These synergistic effects are believed to be the reason why the life of the punch (Comparative Example 6) that was still hard chrome plated was increased from about 1 month to about 4 months, which is 4 times that of the punch (Example 5) surface-treated by the method of the present invention.

[0226] Furthermore, as a punch for forming used in the tablet manufacturing device, there are also those that are coated with diamond-like carbon (DLC) instead of the above-mentioned chrome plating. Although it is recognized that DLC coating also prolongs the life to a certain extent, it is impossible to extend the life to 4 times that of hard chrome plating like the punch surface treated by the method of the present invention, and the life extension corresponding to the cost increase cannot be obtained. Therefore, it can be said that the punch surface treated by the method of the present invention (Example 5) has a superior effect compared with the punch coated with DLC.

Claims

1. A method for surface treatment of a food contact component, characterized in that: A pretreatment step is performed, wherein the pretreatment step is to spray carbide powder of #220 to #800 (JIS R6001-1973) at a spray pressure of 0.2 MPa or more on the contact surface of the food contact component which is made of stainless steel or a material containing stainless steel as a base material and contacts the food, so that the carbon element in the carbide powder is diffused to the surface of the food contact component; The instantaneous heat treatment is performed by spraying approximately spherical fine particles of #220 to #800 (JIS R6001-1973) having a hardness equal to or higher than the surface hardness of the contact surface at a spray pressure of 0.2 MPa or more onto the contact surface with the food that has undergone the pretreatment step, so that they collide with each other, thereby causing a local and instantaneous temperature rise at the collision portion; the structure of the contact surface with the food is miniaturized by plastic deformation, and a surface layer is formed on the entire surface of the contact surface, wherein the surface layer has a plurality of arc-shaped recesses and sharp protrusions formed between the recesses. The above-mentioned surface layer is sprayed with powder composed of titanium or titanium alloy of #100 to #800 (JIS R6001-1973) at a spray pressure of more than 0.2 MPa. The above-mentioned sharp convex parts formed between the above-mentioned recesses are crushed by the collision of the powder composed of the above-mentioned titanium or titanium alloy, so that the above-mentioned recesses formed in the above-mentioned surface layer are changed into recesses of smooth shape without sharp convex parts, and the surface layer becomes the contact surface with the above-mentioned food, and titanium oxide is diffused and penetrated into the above-mentioned surface layer. Thereby, the above-mentioned surface layer is composed of the above-mentioned base material and the above-mentioned titanium oxide and the above-mentioned carbon element diffused and penetrated into the base material, and no coating film is formed on the above-mentioned contact surface.

2. The method for surface treatment of a food contact member according to claim 1, wherein: The carbide powder sprayed in the pretreatment step is silicon carbide powder.

3. The method for surface treatment of a food contact member according to claim 1, wherein: The surface layer is formed to have a thickness of about 0.5 μm, and the titanium oxide is activated and adsorbed on the micronized surface structure formed on the surface of the food contact member, and the titanium oxide is diffused and permeated from the surface of the substrate to a depth of about 5 μm inside.

4. The method for surface treatment of a food contact member according to claim 3, wherein: The titanium oxide is diffused and infiltrated into the surface layer to form a gradient structure in which the amount of oxygen bonding is greater near the surface of the food contact member and the amount of oxygen bonding gradually decreases as it moves from the surface to the inside.

Citation Information

Patent Citations

  • Circuit for detecting tape end

    JP1978019008A

  • Manufacture of fluorine-containing resin film-coated steel plate

    JP1997136382A

  • Kitchen product and dishwasher provided with carbon-doped titanium oxide surface layer

    JP2006239489A

  • Highly corrosion-resistant metal parts made of stainless steel, titanium or titanium alloys

    JP3150048U

  • Method for surface-treating mold

    WO2017175463A1